First description of winged stages of Thraulobaetodes Elouard & Hideux 1991 and reclassification of Rhithrocloeoninae (Ephemeroptera, Baetidae) - Kluge, Nikita J. (Zootaxa, 2015)
Larvae, subimagoes, imagoes of both sexes and eggs of Thraulobaetodes cumminsorum Elouard & Hideux 1991 are described based on reared material from north-west of Zambia. Structure and development of genitals testify that Thraulobaetodes Elouard & Hideux 1991 belongs to Rhithrocloeoninae Kluge 2012. According to the newly suggested classification, Rhithrocloeoninae are divided into Thraulobaetodini tribus n. and holophyletic taxon Rhithrocloeonini, which includes Bugilliesia Lugo-Ortiz & McCafferty 1996, Mutelocloeon Gillies & Elouard 1990 and Rhithrocloeon Gillies 1985 (including subgenus Kivuiops Lugo-Ortiz & McCafferty 2007). Structure of egg chorion of Bugilliesia, Mutelocloeon and Rhithrocloeon is described for the first time. Additional imaginal and subimaginal characters of Mutelocloeon are reported.